To find the y-intercepts of the functions \( f(x) = \sqrt{2x + 1} \) and \( g(x) = \frac{\sqrt{2x + 1}}{3} \), we substitute \( x = 0 \) into both equations.
-
For \( f(x) \): \[ f(0) = \sqrt{2(0) + 1} = \sqrt{1} = 1. \]
-
For \( g(x) \): \[ g(0) = \frac{\sqrt{2(0) + 1}}{3} = \frac{\sqrt{1}}{3} = \frac{1}{3}. \]
Thus, the y-intercepts are:
- For \( f(x) \): \( (0, 1) \)
- For \( g(x) \): \( (0, \frac{1}{3}) \)
Therefore, they both have y-intercepts at:
- \( (0, 1) \) for \( f(x) \)
- \( (0, \frac{1}{3}) \) for \( g(x) \)
So, the answer to the question is:
They both have a y-intercept at \( (0, 1) \) for \( f(x) \) and \( (0, \frac{1}{3}) \) for \( g(x) \).